Analisis Faktor Kendala Berwirausaha bagi Lulusan Sarjana Fakultas Teknologi Industri Universitas Kristen Petra - Alvin Maxwell; Karina Agustin (Jurnal Titra, 2022)
In starting a new business or becoming an entrepreneur, one can face many obstacles. This study aims to see what obstacles are experienced by S-1 graduates of the Faculty of Industrial Technology in entrepreneurship. Constraints faced can be seen from what factors influence in starting a new business. At the beginning of the study, the constraint factors in entrepreneurship were collected through previous research. The constraint factors that have a relationship with building a new business are as follows: entrepreneurship planning, Internal, leadership, environment. The method used to collect data in this research is by distributing questionnaires to graduates of the Faculty of Industrial Technology. The number of respondents obtained is 98 people who come from 4 study programs. Analysis of the results of the questionnaire using Structural Equetion Modeling with SmartPLS 3.0. shows that entrepreneurship planning has no significant effect on entrepreneurship constraints. Meanwhile, Internal, leadership, and environmental factors significantly influence or have an impact on the obstacles that may be faced in entrepreneurship.